Pengembangan SDM Desa Semingkir Melalui Pelatihan Public Sepeaking: Pengabdian - Hauzan Syuraih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) in Semingkir Village was carried out under the theme “Enhancing Human Resources through Public Speaking Training.” This program was motivated by the low communication skills among the community, particularly the younger generation, who often lacked confidence when speaking in public. The activity focused on public speaking training using a participatory method, including interactive lectures, group discussions, simulations, practice sessions, and mentoring. The training took place at the Semingkir Village Hall and involved approximately thirty participants consisting of youth organization members, high school students, and local residents. The results showed significant improvement in participants’ confidence and communication skills. Those who were initially hesitant became able to manage their voice, use body language effectively, and express their ideas more clearly. The final evaluation indicated that most participants were satisfied and motivated to continue practicing. Thus, this training made a tangible contribution to improving human